Hiding in plain sight – recovering clusters of galaxies with the strongest AGN in their cores. Issue 4 (23rd November 2016) - Green, T. S.; Edge, A. C.; Ebeling, H.; Burgett, W. S.; Draper, P. W.; Kaiser, N.; Kudritzki, R.-P.; Magnier, E. A.; Metcalfe, N.; Wainscoat, R. J.; Waters, C.
Abstract: A key challenge in understanding the feedback mechanism of active galactic nucleus (AGN) in Brightest Cluster Galaxies (BCGs) is the inherent rarity of catching an AGN during its strong outburst phase. This is exacerbated by the ambiguity of differentiating between AGN and clusters in X-ray observations. If there is evidence for an AGN then the X-ray emission is commonly assumed to be dominated by the AGN emission, introducing a selection effect against the detection of AGN in BCGs. In order to recover these 'missing' clusters, we systematically investigate the colour–magnitude relation around some ∼3500 ROSAT All-Sky Survey selected AGN, looking for signs of a cluster red sequence. Amongst our 22 candidate systems, we independently rediscover several confirmed systems, where a strong AGN resides in a central galaxy. We compare the X-ray luminosity to red sequence richness distribution of our AGN candidate systems with that of a similarly selected comparison sample of ∼1000 confirmed clusters and identify seven 'best' candidates (all of which are BL Lac objects), where the X-ray flux is likely to be a comparable mix between cluster and AGN emission. We confirm that the colours of the red sequence are consistent with the redshift of the AGN, that the colours of the AGN host galaxy are consistent with AGN, and, by comparing their luminosities with those from our comparison clusters, confirm that the AGN hosts are consistent with BCGs.